(untitled) (Acta Scientiarum. Health Sciences, 2020)
The purpose of this study was to analyze skin temperature (Tsk) responses after a short-term maximum effort test in middle-distance runners. A quasi-experimental study was conducted with ten men (age 23.5±5.10 years) who trained 5 days per week, 2 to 3 hours per day, and were submitted to thermographic evaluation before and after Cooper’s 12-minute run test (CRT). The mean temperature of the anterior-superior, posterior-superior, anterior-inferior, and posterior-inferior regions was compared between the sides (i.e., left and right) before and after CRT. The paired t-test showed a significant decrease in Tsk after CRT in the following regions: right pectoralis major (-3.4%), left pectoralis major (-3.4%), and abdomen (-5%) in the anterior-superior view (p<0.01); and in the upper right trunk (-1.9%), upper left trunk (-1.9%) and lower back (-2.9%) in the posterior-superior view (p<0.05). In the lower limbs, a significant increase in temperature of the left knee (1.6%), and right (3.6%) and left ankles (2.9%) in the anterior view (p<0.05), as well as in the right (4.3%) and left ankles (3.7%) in the posterior view (p<0.05) were observed. There was no difference in temperature between the right and left sides. In conclusion, the Tsk change of middle-distance runners was symmetrical between sides, decreasing in upper limbs and trunk and increasing in lower limbs after a short-term maximum effort test.